Perceived nutritional status, body satisfaction, and fad dieting among middle-adolescent students of the University of the Philippines Rural High School - Don, Sarah Marie A. (Journal of Human Ecology, 2020)
Adolescents are at the stage when they are most influenced, and body image and satisfaction with one’s appearance are formed. At the same time, exposure to health risks of under and over nutrition, and unrealistic body image portrayed in the media and peers put adolescents into a vulnerable position to try popular quick strategies such as fad dieting to achieve their body goal. The objectives of this study are to investigate prevalence of fad dieting among middle-adolescent students in University of the Philippine Rural High School (UP RHS) and determine the factors that influence its practice. The practice of fad dieting, actual and perceived nutritional status (NS) among UP RHS students were obtained through survey questionnaire and anthropometric measurements.